Production of arachidonic acid from candida krusei - Nurul Izyani, Abdul Manan (2012)
The potential of arachidonic acid (AA) in pharmaceutical field had been discovered for a long time. AA is known as a fatty acid that can help information transfer of nerve systems, other than involves in growth and repair of skeletal muscle tissue. Microorganisms such as yeasts are one of the sources that can be commercialized as AA producer. By using microorganisms, the production process become less complicated compared to using animal source, and the ‘Halal’ standard can be fixed. The works done in this research investigate the optimum condition for AA production from yeast. In this research, the best culture condition that produced the highest yield of AA was determined by varying the pH, the carbon source and the agitation speed. The range of pH is 5 to 9. The carbon sources that were used are sucrose, starch and the mixture of sucrose and starch. Speed of incubator shaker was set at 50 rpm, 150 rpm and 250 rpm. Extraction of lipid was done by using twostep Bligh and Dyer (1959) method. Chloroform and methanol were added in specific ratio before centrifugation. The lower phase which contain lipid was collected. After evaporation, the lipid extract was dissolved in small volume of chloroform and methanol. The lipids obtained were analyzed in gas chromatography. The highest dry biomass concentration was produced at a culture at pH 7 and 250 rpm agitation rate by using sucrose while the highest yield of AA was produced at pH 7 and 150 rpm agitation rate by using sucrose as carbon source. AA production from yeast had shown advantages over other sources. Further studies on optimization of AA production should be directed at varying other significant parameters including nutrients needed and method of extraction. The findings in this study will be helpful for other research about AA in the future.